2014
DOI: 10.1111/1745-8315.12143
|View full text |Cite
|
Sign up to set email alerts
|

Process‐orientated psychoanalytic work in initial interviews and the importance of the opening scene

Abstract: From the very first moment of the initial interview to the end of a long course of psychoanalysis, the unconscious exchange between analysand and analyst, and the analysis of the relationship between transference and countertransference, are at the heart of psychoanalytic work. Drawing on initial interviews with a psychosomatically and depressively ill student, a psychoanalytic understanding of initial encounters is worked out. The opening scene of the first interview already condenses the central psychopathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Using a psychoanalytic method and analysis allowed for consideration of the “entirety of the interactions” (Wegner, 2014), and in doing so, accessed additional sources of information beyond the manifest layer of the words exchanged. This method proved to be a good fit for the topic of research chosen, as hoarding and belongings were rarely directly addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Using a psychoanalytic method and analysis allowed for consideration of the “entirety of the interactions” (Wegner, 2014), and in doing so, accessed additional sources of information beyond the manifest layer of the words exchanged. This method proved to be a good fit for the topic of research chosen, as hoarding and belongings were rarely directly addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Several analysts have suggested that initial encounters are disturbing in ways that we do not consciously perceive but that both participants, unconsciously or preconsciously, register and react to (Ogden 1992;Rothstein 1995;Ehrlich 2004Ehrlich , 2010Ehrlich , 2013Levine 2010). Findings from qualitative research by the Working Party on Initiating Analysis (clinical workshops studying initial interviews) provide further support for this view: (1) regardless of how tranquil it might appear, the initial encounter between the patient's and the analyst's intense fears and wishes precipitates an emotional storm (Reith 2010(Reith , 2012Reith et al 2012) ; (2) for analysis to begin, the analyst must bear the initial transference/countertransference and transform it into a beginning appreciation of the patient's suffering and its meaning (Reith 2012;Vermote 2012) ; (3) which patient is analyzable is determined not by objective criteria but by whom the analyst thinks it possible to work with (Møller 2014;Wegner 2014). Observing that analysts in the workshops often disagreed as to which patient should be offered analysis, Møller (2014) concludes that "it is something in the individual analyst's way of reacting to the patient that determines the outcome, and not some constant called analyzability" (p. 494).…”
Section: Fears In the Initial Consultationmentioning
confidence: 99%